A spear flap surgical revision - De Piano, Ernesto; Rubegni, Pietro; Cioppa, Vittoria (Dermatology reports, 2024)
A 55-year-old male presented with a recurrent infiltrative basal cell carcinoma of the right nasal ala. Previous incomplete excision was repaired with second intention healing resulting in a contracted ala with columellar deviation and nostril asymmetry. [...]